Modernization of the Legal System of Ukraine: Sociocultural Dimension - Hladkyi S. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the research is the theoretical characterization of some external system connections that determine the functional state of the legal system of Ukraine and are able to play a decisive role in the process of its modernization. These connections are conceptually understood in the socio-cultural dimension of Ukrainian society. Methodology. The research methodology is based on the principle of systematicity. It is based on the analysis and generalization of the available empirical and theoretical experience of the author on the research topic, as well as the formulation of relevant conclusions and recommendations. The following main methods were used to solve individual research tasks: systemic (functional and structural), historical, sociological (phenomenological). Results. The existence of a stable tendency to weaken the regulatory influence of the law was ascertained. This trend is the result of significant changes in the general system of social regulation of social relations in Ukraine in the 20th century and at the beginning of the XXI century. The legitimate behavior of social subjects is considered as a synergistic effect of the functioning of a complex of social regulators. A brief description of the functional capacity of such of them as law, morality and religion is given. The national mentality is interpreted as a system-forming factor of the entire system of social regulation. It is proposed to consider the characteristics of the national mentality as a constant and a determining factor when choosing a strategy for the modernization of the national legal system. Originality. The importance of the synergistic effect in the regulation of social behavior is emphasized. The need for a realistic assessment of the spiritual and cultural state of Ukrainian society and its consideration in the process of developing programs and strategies for the modernization of the national legal system, including European integration, is emphasized. Practical significance. The results of the study can be used in the process of developing educational standards and educational programs for the training of lawyers, as well as in the field of developing the principles of legal policy in Ukraine.